2018
DOI: 10.1155/2018/7645726
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamic Stiffness of Bridge Cap‐Pile System

Abstract: In order to investigate the applicability of dynamic stiffness for bridge cap-pile system, a laboratory test was performed. A numerical model was also built for this type of system. The impact load was applied on the cap top and the dynamic stiffness was analysed. Then, the effect of the effective friction area between pile and soil was also considered. Finally, the dynamic stiffness relationship between the single pile and the cap-pile system was also compared. The results show that the dynamic stiffness is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Ma et al [13] also measured the dynamic stiffness for 680 bridge piles and found that an obvious positive correlation exits between the dynamic stiffness and bearing capacity of intact piles. To consider the influence of pile cap in the method, Chu et al [20] performed a laboratory test and a numerical model to investigate the dynamic stiffness of the cappile system. In addition, the dynamic stiffness index was also employed to detect the void behind the tunnel linings [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [13] also measured the dynamic stiffness for 680 bridge piles and found that an obvious positive correlation exits between the dynamic stiffness and bearing capacity of intact piles. To consider the influence of pile cap in the method, Chu et al [20] performed a laboratory test and a numerical model to investigate the dynamic stiffness of the cappile system. In addition, the dynamic stiffness index was also employed to detect the void behind the tunnel linings [21].…”
Section: Introductionmentioning
confidence: 99%